Actor and Partner Effects of Touch: Touch-Induced Stress Alleviation Is Influenced by Perceived Relationship Quality of the Couple - Liu, Difei; Piao, Yi; Ma, Ru; Zhang, Yongjun; Guo, Wen; Zuo, Lin; Liu, Weili; Song, Hongwen; Zhang, Xiaochu (Frontiers in Psychology, 2021)
Because of the impact of close partner's touch on psychological and physical well-being by alleviating stress, it is important to explore the influence factors that underlie the stress-alleviating effect of close partner's touch. Previous studies suggested that the stress-alleviating effect was different when individuals were touched by different persons. Specifically, the stress was reduced significantly when the individual was touched by the close partner compared with the acquaintance and the stranger. However, whether the stress-alleviating effect of touch was modulated by the close relationship quality is unknown. To examine this question, the participants (n = 61) performed a 3 (i.e., alone, partner no-touch, and partner touch) × 2 (i.e., safety and threat) within-subjects experiment. The results revealed that the stress of the participants alleviated significantly while close partners present with touch compared with without touch during facing a threat. We also found that the relationship quality of couple-members (i.e., participants perceiving the quality of alternatives and the partners' commitment level) modulated touch-induced stress alleviation. Participants perceiving the low quality of alternatives and the high partners' commitment level showed stronger touch-induced stress-alleviating effect than participants perceiving the high quality of alternatives and the low partners' commitment level. The explained variance was around 16.8% jointly for actor and partner effects. These findings provide evidence for explaining the reasons for touch-induced alleviating stress and have important implications for predicting the future effect of interactive behaviors.